Efficacy of Topical Clobetasol Propionate 0.05% Ointment and Topical Tacrolimus 0.1% Ointment in Treatment of Alopecia Areata.: RCT - Farman Ullah, Muhammad Dawood, Nasma Noor, Sadia Hameed (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Non-scarring hair loss from the scalp or body occurs as a result of alopecia areata. It is the most prevalent autoimmune disorder. Aims: To compare the efficacy of topical clobetasol propionate 0.05% ointment and topical tacrolimus 0.1% ointment in the management of localized alopecia areata. Study design: Randomized control trial. Methodology: All patients (n=116) having alopecia areata of the scalp were included. SALT Score was calculated at presentation. Group A received topical clobetasol propionate 0.05% ointment applied twice daily over the alopecia patch and group B received topical tacrolimus 0.1% twice daily for 3 months. Patients were followed in OPD at 1month, 2months and 3months interval to ensure compliance. All this information was recorded on Performa. Data was analyzed using SPSS version 26. Efficacy of both groups was compared using Chi square test and keeping P-value of ≤ 0.05 as significant. Results: As per efficacy, in Group A, 46 (79.31%) patients showed effective results whereas in Group B only 26 (44.82%) patients showed effective results with a significant P-value of 0.00013. Conclusion: It was concluded that topical clobetasol propionate 0.05% ointment was more effective as a treatment option in promoting hair re-growth among patients of alopecia areata.